Steganographic access control in data hiding using run‐length encoding and modulo‐operations. Issue 2 (16th June 2011) - Lee, Chin‐Feng; Weng, Chi‐Yao; Sharma, Aneesh
Abstract: The vast potential of information and communication technologies such as computer‐based communication networks and telecommunication systems is indeed blooming innovations. This paper is a novel attempt in the field of authorization and access control, which uses steganography that coverts the data into a form that cannot be interpreted by unauthorized persons. The proposed algorithm transfers compressed data and hides it into a cover medium by improvising existing run‐length technique in steganography. It deals with a compression technique that uses the redundancy feature of a bitstream and then uses this compressed stream to embed data in an image. The run‐length encoding technique is exploited to compress a bitstream being embedded in a cover image. However, run‐length encoding method has inefficient compression like the sharp bitstreams, such as the pattern "101010101". This study developed a novel high‐capacity steganographic access control in data hiding to transform sharp bitstreams into smooth bitstreams before it is hidden into a cover image. Our scheme performs the logical Exclusive‐OR (XOR) operation to smoothen the secret bitstream and to embed the result into a cover medium. Additionally, the proposed scheme employs generalized difference expansion transform for image recovery after data extraction; consequently, the image fidelity can be preserved. The experimental results show that our scheme owns a higher embedding capacity than previous approaches while maintaining high image quality. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : This study developed a novel high‐capacity steganography to transform sharp bitstreams into smooth bitstreams before it is hidden into a cover image. Additionally, the proposed scheme employs generalized difference expansion transform for image recovery after data extraction; consequently, the image fidelity can be preserved.